THE IMPLEMENTATION OF INDONESIA'S NATIONAL QUALIFICATIONS FRAMEWORK HAS GRADUALLY SHIFTED ITS EMPHASIS FROM COMPETENCY DEVELOPMENT TOWARD COMPETENCY VALIDATION. (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Indonesia's National Qualifications Framework (IQF/KKNI), established under Presidential Regulation No. 8 of 2012, was designed to integrate competencies acquired through formal education, non-formal education, vocational training, work experience, and lifelong learning into a unified national qualification system. The framework was originally intended to promote continuous competency development while recognizing learning outcomes obtained through multiple pathways. However, its implementation has gradually shifted its emphasis from competency development toward competency validation, with competency certification increasingly functioning as a mechanism for verifying existing competencies rather than facilitating continuous capability enhancement. This implementation shift has narrowed the strategic role of the National Qualifications Framework in supporting lifelong learning, workforce development, and inclusive productivity. This study examines the philosophical and regulatory foundations of Indonesia's National Qualifications Framework to identify the factors contributing to this implementation shift and its implications for competency policy. The study employs a qualitative conceptual research design integrating doctrinal legal analysis, conceptual policy analysis, and a systematic review of competency development and National Qualifications Framework literature. The analysis indicates that the current implementation places greater emphasis on competency assessment and certification than on structured competency development through education, vocational training, workplace learning, and Recognition of Prior Learning (RPL), thereby creating a conceptual inconsistency with the original philosophy of the framework. The study argues that competency certification should function as the outcome of continuous competency development rather than its primary objective. Accordingly, it proposes a reinterpretation of the implementation philosophy of Indonesia's National Qualifications Framework by restoring competency development as its central orientation. This reinterpretation contributes to the international discourse on National Qualifications Frameworks by providing a policy perspective on how implementation shifts can alter the original objectives of qualification systems and offers recommendations for strengthening lifelong learning, workforce capability, and sustainable productivity.